Effect of Normal Saline Bicarbonate on Reversing Epidural Anesthesia Either with Bupivacaine Or Bupivacaine and Nalbuphine in Patients Undergoing Orthopedic Surgery. (2nd March 2015) - Attia, Josef; Mohamed, Ahamed; Bader, Yaser
Abstract : Background . Orthopedic procedures are among the commonest surgeries in the elderly. On the other hand, those patients have many risk factors suitable for development of postoperative complication due to prolonged postoperative recumbent that decrease by using anesthesia technique allowed early ambulation as far as possible.   Aim of the Work . The aim of this study was to evaluate whether washout of the local anesthesia with 0.9% normal saline with bicarbonate through the epidural catheter could provide early ambulation throughout the faster recovery of the motor block. Patient and Methods . Sixty adult patients were included in this study and divided into three groups. In group I, epidural injection of bupivacaine was carried out without wash (control group). In group II, epidural injection of bupivacaine was followed by wash. In group III, epidural injection of both bupivacaine and nalbuphine was followed by wash. Results . They were significantly faster in both group II and group III as compared with group I. In group I, sensory recovery was insignificantly faster than the motor recovery. In group II motor recovery was significantly faster than sensory recovery. In group III motor recovery was significantly faster than the sensory recovery. Conclusions . These results suggested that early ambulation with an adequate postoperative analgesia was reported in patient receiving epidural injection of both bupivacaine and nalbuphine.